PELESTARIAN KEARIFAN LOKAL CANANG SARI SEBAGAI PERSEMBAHAN DALAM KEGIATAN RITUL DAN UPACARA ADAT - Nisa, Fitria Khoirun; Sulistiono, Bambang; Aliyah, Siti; mumpuni, Atikah (Widya Pustaka : Jurnal Ilmiah Pendidikan, 2025)
Canang sari as a ritual tool for Balinese Hindu communities outside the island of Bali is still maintained even though the materials used are different. This research aims to find out the local wisdom of canang sari as a ritual offering for Hindu communities in Bali. The method used is a qualitative method. The results of this research show that the tradition of offering canang sari is still maintained to this day, because canang sari is a special attraction for Hindus to use it in ritual offerings for traditional ceremonies. Even though in the current era of modernization, the Hindu community in Bali still preserves the local wisdom of canang sari by making it using natural materials that come from nature such as flowers which have many colors, leaves, areca nut, sugar cane, and gambier in each piece of flower and leaf which is arranged carefully, showing a deep spiritual message, a sign of unity. nature, spirit and God. Making canang saris is usually called matanding and majejahitan. All Balinese people are taught to make canang saris from childhood to adulthood, with the aim being that these canang saris will be preserved for generations to come. Canang sari also has five meanings and objectives, namely to practice the teachings of the Veda, to show gratitude to Sang Hyang Widi, to improve one's quality, and as a way to get closer to God who is worshiped.